The Influence of Corporate Social Responsibility, Tunneling Incentive, and Capital Intensity Against Tax Avoidance - Excellent Nokiyanti; Widi Dwi Ernawati; Indrayati (Politeknik Negeri Malang, 2023)
The research aimed to analyze the influence of Corporate Social Responsibility, Tunneling Incentive, and Capital Intensity on Tax Avoidance in energy subsector companies for a five-year period. The research design was explanatory quantitative to examine the relationship of variables using multiple linear regression. The study used Purposive Sampling as the data collection technique. From the 53 companies, there were only 14 companies which met the criteria. The data collected were financial statements, annual reports and sustainability reports of energy sub-sector companies listed on the IDX for the period of 2017-2021. The data analysis tool employed was the 22th version of IBM SPSS. The results of this research showed that partially, the Corporate Social Responsibility variable had no significant effect on Tax Avoidance. Conversely, Tunneling Incentive and Capital Intensity affected Tax Avoidance significantly. In addition. the results of the simultaneous test revealed that all the variables, the Corporate Social Responsibility, Tunneling Incentive and Capital Intensity had a significant impact on Tax Avoidance.